The Prenatal Yoga on Perineal Rupture and Duration of Stage II - Rahayu, Budi; Solihah, Nur Rahmawati (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Contractions that are disturbed due to tension in smooth muscles and blood vessels cause stiffness of the cervix, causing perineal rupture and also the lack of progress in the labor process, especially the second stage, which will increase maternal and infant morbidity and mortality. Prenatal yoga is an exercise using slow movements combined with breathing exercises to maintain the mother's posture during pregnancy, preparing for the birth process by reducing the sensation of pain with breathing exercises. The aim of this research was to examine the effect of prenatal yoga on perineal rupture and the duration of the second stage of labor. This study used a quasi-experimental design with a post-test control group. A total of 42 pregnant women participated in this study. The participants were divided into two groups: a control group and a treatment group. The sampling technique used was purposive sampling. Data were analyzed using the Mann-Whitney test. The results of this study indicated that the p-value was 0,00 <0,05 for perineal rupture and the p-value was 0,01 <0,05. These results indicated that there are differences in perineal rupture and duration of kala II between the control group and the treatment group. The Conclusion is that there is an effect of prenatal yoga on perineal rupture and length of stage II. Pregnant women can empower themselves by doing prenatal yoga so that labor is minimally traumatic and smooth.